Incomplete ossification of the humeral condyle as the cause of lameness in dogs - Meyer-Lindenberg, A.; Heinen, V.; Fehr, M.; Nolte, I. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
In a retrospective and prospective trial over six years, 17 joints from 13 dogs presented with incomplete ossification of the humeral condyle (IOHC) were included. All dogs showed lameness of the forelimb but no humeral condylar fractures. One dog showed a fracture of the olecranon. Four of the bilaterally affected dogs showed only unilateral lameness. 53.8% of the dogs (7/13) were younger than one year. With regard to breed distribution, the German Wachtel was most frequently represented with three dogs. In 12 dogs the diagnosis was made by radiography in a craniocaudal view, and seven dogs could be further investigated by computed tomography. In one dog the diagnosis was only made during arthroscopy. Two joints showed an additional fragmented medial coronoid process of the ulna and another two an osteochondrosis dissecans of the medial humeral condyle. During arthroscopy, all joints showed a clearly visible fissure line in the joint cartilage between the humeral condyles. In ten joints the I0HC was treated with a transcondylar lag screw under arthroscopic control. Three of the four bilaterally affected dogs were treated only unilaterally because of a lack of lameness on the other side. In the dog with the olecranon fracture, only the fracture was treated. The patients were rechecked clinically and radiologically (n = 10) or by means of a questionnaire (n = 1) at an average of 26 months post operation. Seven cases, six of them treated by lag screw fixation, did not show any lameness. Three joints (one dog with olecranon fracture, two unilaterally affected dogs with lag screw fixation) showed some degree of lameness after heavy strain and one dog showed a continuous slight lameness. The four bilaterally affected and only unilaterally treated dogs showed no lameness on the untreated joint. With regard to development of arthrosis, six radiographically examined joints showed no increase in arthroses. In five joints the increase was mild and in two joints moderate. In six joints with lag screw fixation, the IOHC was radiographically unified and was confirmed by computed tomography in three cases.
Keywords: Incomplete ossification of the humeral condyle; IOHC; dog; occurrence; treatment; results